Penerapan Metode Mind Maping untuk Meningkatkan Hasil Belajar Kelas III di SD Negeri 33 Mataram - Lidiawati, Linda; Witono, A. Hari; Lestari, Sri (TSAQOFAH, 2023)
The Mind Mapping type learning method can realize changes, from a teacher-oriented learning approach (teacher centered approach) to a student-oriented learning approach (student centered approach). The aim of this research is to determine the use of the mind mapping method in improving learning outcomes. This research includes classroom action research using three research cycles. The research was conducted at SDN 33 Mataram with a class IIIA sample of 21 students. Based on the results of the analysis, it can be concluded that there was an increase in student learning outcomes from the Minimum Completeness Criteria of 60 in the first cycle, the percentage of students who reached the KKM was 52.3%, in the second cycle, the percentage of students who reached the KKM was 71.4%. Likewise, in the third cycle, the percentage of students reached 85.7%. Thus, it can be concluded that there has been an increase in learning outcomes for class III students at SDN 33 Mataram.